BELAJAR DARI RUMAH (BDR) MASA PANDEMI COVID-19 PADA LEMBAGA PENDIDIKAN DASAR DI KABUPATEN LOMBOK TIMUR - Salimul Jihad; Nirwana Puspasari; Muhammad Nurman (Universitas Islam Negeri Mataram, 2023)
This study aims to explain the implementation of learning and assessment during the Covid-19 pandemic in elementary school education units (SD) in East Lombok Regency. This study uses a qualitative research method with a phenomenological approach. The use of this method is based on the reason that this research focuses on the reality of BDR. Meanwhile, the phenomenological approach aims to find out the reality, strategic management of BDR, and the implications of BDR through this phenomenological study. As a result of implementation in the field, schools use various methods and tools to facilitate student learning at home according to the abilities and circumstances of students, teachers and parents of students. Broadly speaking, Distance Learning (PJJ), which is part of Learning From Home (BDR), is carried out using various approaches, namely: 1) Online/online distance learning. This learning uses gadgets and laptops through several portals and online learning applications; 2) Remote/offline (during) distance learning, using television, radio, self-learning modules and worksheets, printed teaching materials, teaching aids and learning media from objects in the surrounding environment. The implementation of PJJ in accordance with this approach, which actually occurs in the field, is very diverse. There are schools that can carry out these two approaches well, there are schools that combine these two approaches which is termed